2021
DOI: 10.1017/s1049023x21001333
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Characteristics of Humanitarian Health Education and Training Programs: A Web-Based Review

Abstract: Introduction: Education and training programs are critical to achieve personnel capacity building and professionalization in the rapidly growing humanitarian health sector. Thus, this study aimed to describe the status of humanitarian health education and training programs world-wide. Methods: A web-based analysis was conducted to identify the available humanitarian health programs. The following characteristics of the training programs were described: geographical location, target audie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Unfortunately, in the field of global health, particularly in humanitarian health and disaster medicine, the target audiences are poorly defined [5]. Moreover, the lack of a coherent competency framework or standardized curriculum creates a challenge in defining the training needs and learning objectives [5]. In addition, global health training is rarely incorporated into undergraduate medical and health education programs.…”
Section: Challenges and Practical Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, in the field of global health, particularly in humanitarian health and disaster medicine, the target audiences are poorly defined [5]. Moreover, the lack of a coherent competency framework or standardized curriculum creates a challenge in defining the training needs and learning objectives [5]. In addition, global health training is rarely incorporated into undergraduate medical and health education programs.…”
Section: Challenges and Practical Solutionsmentioning
confidence: 99%
“…Despite the growth of training opportunities in global health, the limited availability, unequal geographical distribution, and predominance of theoretical teaching methods in available training programs combined with high tuition fees [4,5] constitute barriers to health workforce capacity building, especially where it is needed the most [5]. Innovative digital technologies and strategies, such as electronic simulation (e-simulation) [6], could address these gaps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For teaching humanism and professionalism, the best is modeling it and the example of the Baylor College of Medicine (BCM), which "adopted" virtually all the medical students of Tulane University School of Medicine and continued their education for 8 months after most of New Orleans was flooded on August 29, 2005, after Hurricane Katrina, in which, after the BCM-Tulane experience, BCM developed a disaster-management plan that could help other schools as they plan for disasters [11]. Some authors have identified training programs, most of them available in few countries of the global North, and few qualified for a master's degree in humanitarian health using theoretical knowledge as the most common method used for teaching and assessment, but the duration of the training and tuition fees were different for different programs and qualifications, while target audience, prerequisite, and curriculum design were often vaguely described or missing [12].…”
Section: Introductionmentioning
confidence: 99%